A matched‐pair analysis reveals marginally reduced CD34+ cell mobilization on second occasion in 27 related donors who underwent peripheral blood stem cell collection twice at the same institution. Issue 11 (18th October 2019) - Velier, Melanie; Granata, Angela; Bramanti, Stefania; Calmels, Boris; Furst, Sabine; Legrand, Faewzeh; Harbi, Samia; Faucher, Catherine; Devillier, Raynier; Blaise, Didier; Mfarrej, Bechara; Lemarie, Claude; et al.
Abstract : BACKGROUND: In a small proportion of cases, hematopoietic function is insufficient after allogeneic hematopoietic stem cell transplantation, as a result of poor graft function or graft failure. These complications are common indications of re‐mobilization of the initial donor, either for a second allograft or for an infusion of CD34+ Selected stem Cell Boost (SCB). METHODS AND MATERIALS: We retrospectively reviewed the results of two cycles of CD34+ cell mobilization and collection. CD34+ cells mobilized and collected at each cycle were compared. When CD34+ cell selection from the collected allogeneic mononuclear cells was indicated, it was performed with the Clinimacs Plus® medical device, and results from in‐process and final quality checks were analyzed. To assess the efficacy of CD34+ SCB, transfusion needs before and after the infusion of selected CD34+ cells were calculated. RESULTS: The median peripheral blood concentration of CD34+ cells/μL was marginally reduced during the second cycle (35.6 vs 33.8, p < 0.05); results revealed a strong correlation between paired values (r = 0.85). The cumulative number of collected CD34+ cells were similar for both cycles; the total processed blood volume was higher during the second cycle (p = 0.023). For CD34+ immune‐selection procedures, CD34+ cell recovery and purity were respectively 57% and 95%, with a median T‐cell depletion of 6.7 log. Recipients' needs for platelet and red blood cell transfusions were significantly reduced after CD34+ SCB. CONCLUSION: This study confirms the feasibility of a second cycle of mobilization in healthy related donors and the benefits of CD34+ SCB on hematopoietic reconstitution.